Penetapan Kadar Klorida pada Air Sumur di STIKes Guna Bangsa Yogyakarta Tahun 2013 - Dian Wuri Astuti; Siti Fatimah; Rausyanah Fikriyyah (Journal of Health (JoH), 2014)
Background : STIKes Guna Bangsa Yogyakarta was a health college which used well water as source of clean water for many needs, one of them use as drinking water. Contamination the source of water in STIKes Guna BangsaYogyakarta can occur cause activity of waste disposal directly into the land so that can give effect to quality of the water source well. The good water must be having four criteria or parameter. The first is physic parameter involve dissolved solid, turbidity, smell, taste, colour and temperature. Second parameter, biology parameter was involved type and contents of microorganism. Third parameter is radioactive was involved radioactive substance. The fourth there’s chemical parameter, it was involved many types of ion, dissolve oxygen or toxic compounds likes chloride. Chloride ions in the form of inorganic anion Cl- is a lot there in the water. The presence of excessive chloride in water can cause interference with the physical properties of water, disruption of metal pipes, and health problems. Lack of chloride element in body will be bring about the fall in value of the extracellular fluids osmotic and if excess, will be damage the kidney. Therefore, the writer interested to know of chloride rate in well water and choose title “Penetapan Kadar Klorida pada Air Sumur di STIKes Guna Bangsa Yogyakarta”. Examination of chloride in well water conducted to determine howlarge concentration of chloride content in well water, drinking water requirements are allowed in PerMenKes RI No. 492/MenKes/Per/IV/2010. Method : Chloride concentration in well water determined by Argentometry Mohr with standard solution of AgNO3 and K2CrO4 indicator, the titration end point is marked with red brick precipitation of Ag2CrO4. This research was descriptive research laboratory test. The sample in study was well water in Guna Bangsa Yogyakarta’s STIKes. Data analysis result of research done descriptively in table or graphic form. Result : Chloride concentration in well water of Guna Bangsa Yogyakarta’s STIKes with sample as many as 9 sample showed that accordance with PerMenKes RI 2010 were not exceed the maximum limit was 250 mg/L. Conclution : The sample of well water in Guna Bangsa Yogyakarta’s STIKes had chloride concentration were according with allow quality of clean water in accordance with PerMenKes RI No. 492/ Menkes/ Per/ IV/ 2010.